The use of Nigella sativa as a single agent in treatment of male infertility - M. Marbat, Mossa; abid Ali, Mohmed; M. Hadi, Azzawi (Tikrit Journal of Pharmaceutical Sciences, 2023)
Infertility is a condition defined by the failure of the wife to achieve a successful pregnancy after 12 months or more of regular unprotected intercourse. About 1 in 7 couples have problems conceiving, with a similar incidence worldwide. Over 80% of couples who have regular sexual intercourse and do not use contraception will achieve a pregnancy within one year. The aim of this was to investigate the effect of Nigella sativa on male infertility. This study is a case control longitudinal clinical study. It was conducted on 55 infertile men with age range from 18-40 years from December 2011 to December 2012. The patients included were those who attended the clinics of specialist urologist, who are complaining of infertility with low sperm count or quality. Forty patients from the total 55 patients (15 patients withdraw from the study for many reasons) who were complete the whole treatment trial were included in this study. 40 infertile men were treated with N. sativa Capsule 2g per day. Semen parameters, serum Follicle stimulating hormone (FSH), Luteinizing hormone (LH) and testosterone were measured before and after 3 months of treatment with N. sativa. Sperm count was significantly increased after 3 months of treatment with N. sativa. The percentage of actively moving sperms was significantly increased after 3 months of treatment with N sativa. The semen volume was significantly increased after 3 months of treatment with N sativa. The sperms viability was significantly increased after 3 months of treatment with N. sativa. Sperms normal morphology was significantly increased after 3 months of treatment with N. sativa. Serum FSH, LH and testosterone levels were significantly increased after 3 months of treatment with N. sativa. These results supported by many studies published that explained and concluded the effect of N. sativa on semen quality. The present study conclude that N. sativa can be used as a single agent for treatment of male infertility.